Tracker Outdoor untuk Penyandang Down Syndrome - Hanif, Nasywan; Hanuranto, Ahmad Tri; Dewanta, Favian (eProceedings of Engineering, 2024)
Indonesia has a significant number of individuals with Down Syndrome, including those with mobility and mental impairments. This group is particularly vulnerable to the risk of getting lost, especially during emergencies such as natural disasters or evacuations. They often face difficulties in ensuring their own safety and communicating when lost. Therefore, it is crucial to develop effective monitoring solutions. A LoRa-based GPS Tracker emerges as a potential solution for tracking them, especially in dangerous locations where terrain hinders signal reception. This technology offers reliable tracking capabilities even in areas with weak signals. The real-time, portable LoRa-based GPS Tracker enables accurate location monitoring in challenging terrains and overcomes mobile signal limitations. This system allows continuous monitoring without relying on cellular networks, thereby reducing the risk of losing track. In this study, a LoRa-based GPS device was developed that can transmit the user’s location coordinates accurately, even in difficult geographical conditions. The LoRa module uses RF signals, providing a stable communication solution in remote areas where cellular signals are hard to reach. Keywords- Down Syndrome, GPS Tracker, LoRa